PENGARUH THIN CAPITALIZATION, CAPITAL INTENSITY, FINANCIAL DISTRESS PADA AGRESIVITAS PAJAK DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Anggraini Fabrila (2022)
This study was conducted to examine the factors that can affect tax aggressiveness such as thin capitalization, capital intensity, financial difficulties. In addition, it also examines the relationship between audit quality in moderating tax aggressiveness with thin capitalization, capital intensity, and financial distress. The population in this study are companies in the industrial sub-sector in 2016-2020. With a total sample of 37 companies. The analysis technique uses panel data regression method. thin capital letters have a positive effect on tax aggressiveness, capital intensity and financial difficulties do not affect tax aggressiveness, audit quality can weaken thin capital letters on tax aggressiveness, audit quality can strengthen capital intensity and financial difficulties on tax aggressiveness.